The effect of Problem-Based Learning Model With Video-Assisted Communication Skills and Creativity of Students in High School Physics - Nia Elvi Rahmawati; Sutrio; Joni Rokhmat; Gunawan (International Journal of Contextual Science Education, 2024)
This research seeks to examine how physics students at SMA Negeri 8 Mataram may improve their communication and creative abilities via the use of problem-based learning models with video support. That which isUsing a non-equivalent control group design, the research adopts a pseudo-experiment approach. The 159 participants in this research are from five different classes in Class X MIA SMA Negeri 8 Mataram during the 2023–2024 school year. We selected Class X MIA 4 (32 students) as our experimental group and Class X MIA 5 (31 students) as our control group using the purposive selection method. A video-assisted problem-based learning model was used by the experimental group for therapy, while a conventional model was employed by the control group. The data processing findings revealed that the control group had strong communication skills (69.70), but the experimental group had an average of 78.52. The control group averaged 76.84 on the creativity test, but the experimental group averaged 83.52. It has Results from the hypothesis test showed that a video-assisted problem-based learning model had a significant effect on both communication (tcount = 0.00) and creativity (tcount = 0.02) abilities, with a significance value of 0.00 for each variable, when we used a MANOVA test to evaluate the data. Thus, it is safe to say that the physics students at SMA Negeri 8 Mataram really benefit from the video-assisted problem-based learning approach when it comes to improving their communication and creative abilities